Efficacy of homeopathic treatment against natural infection of sheep by gastrointestinal nematodes. - da Rocha, Raquel A; Pacheco, Rodrigo Dias L; Amarante, Alessandro F T (My University, 2006)
The efficacy of the homeopathic treatment with the Fator Vermes, administered according to the manufacturer's recommendations, was evaluated against gastrointestinal nematodes infections in sheep. The experiment was divided into two phases: in the first phase (January/06/2004 to April/30/2004), the animals of the treated (n=10) and control (n=10) groups were treated individually with conventional anthelmintics to avoid deaths. In the second phase (April/30/2004 to July/06/2004), the sheep from the group that received the Fator Vermes were treated as they had been in the previous phase, while the control group animals were treated with conventional anthelmintics at 14 day intervals. In the first phase of the experiment, there was no significant difference (P>0.05) between group means regarding egg counts in feces (EPG), weight gain, or packed cell volume (PCV). Meanwhile, in the second phase, the control group sheep had a significantly higher weight gain, higher PCV values, and lower EPG counts. Infective larvae of Haemonchus spp., Trichostrongylus spp., Cooperia spp., and Oesophagostomum spp. were identified in the fecal cultures. After six months of daily treatment with the Fator Vermes, it was not possible to substantiate the product's benefits in both sheep health and productivity or in the prophylaxis of gastrointestinal nematode infections.
Keywords: animal; animal disease; female; homeopathy; intestine infection; nematodiasis; parasitology; sheep disease; stomach disease; Animals; Female; Homeopathy; Intestinal Diseases, Parasitic; Nematode Infections; Sheep Diseases; Stomach Diseases